Issues and challenges of takaful for micro, small, and medium enterprises (MSMEs) in Malaysia - Mohd. Shariff, Ros Aniza; Hassan Mohamed, Zakaria (Emerald Publishing, 2023)
The primary purpose of this paper is to discuss Takaful in Malaysia and how it helps Micro, Small, and Medium Enterprises in Malaysia that suffer financial losses. In addition, this article elaborates on and highlights the main issues and challenges of Takaful for MSMEs in Malaysia. A qualitative method is used in this paper. We mainly conducted library research to study Takaful in Malaysia and the issues and challenges of Takaful for MSMEs in Malaysia. The findings show several issues and challenges of Takaful for MSMEs in Malaysia. Low penetration rate, lack of knowledge and awareness and Micro Takaful issue are the main issues that were found. Therefore, to increase the penetration rate of Takaful for MSMEs, the Malaysian government, and Takaful corporations should develop a comprehensive strategy for Takaful. Additional study is needed in this area. This paper is limited to Malaysia. Therefore, it cannot be generalized to other countries. We collected articles and studies that relate to the topic that were published between 2013 to 2023. We cited the most relevant publications to determine the issues and challenges of Takaful in Malaysian MSMEs.